Neurosurgeon academic impact is associated with clinical outcomes after clipping of ruptured intracranial aneurysms - Alotaibi, Naif M.; Ibrahim, George M.; Wang, Justin; Guha, Daipayan; Mamdani, Muhammad; Schweizer, Tom A.; Macdonald, R. Loch (PloS one, 2017)
Surgeon-dependent factors such as experience and volume are associated with patient outcomes. However, it is unknown whether a surgeon's research productivity could be related to outcomes. The main aim of this study is to investigate the association between the surgeon's academic productivity and clinical outcomes following neurosurgical clipping of ruptured aneurysms. We performed a post-hoc analysis of 3567 patients who underwent clipping of ruptured intracranial aneurysms in the randomized trials of tirilazad mesylate from 1990 to 1997. These trials included 162 centers and 156 surgeons from 21 countries. Primary and secondary outcomes were: Glasgow outcome scale score and mortality, respectively. Total publications, H-index, and graduate degrees were used as academic indicators for each surgeon. The association between outcomes and academic factors were assessed using a hierarchical logistic regression analysis, adjusting for patient covariates. Academic profiles were available for 147 surgeons, treating a total of 3307 patients. Most surgeons were from the USA (62, 42%), Canada (18, 12%), and Germany (15, 10%). On univariate analysis, the H-index correlated with better functional outcomes and lower mortality rates. In the multivariate model, patients under the care of surgeons with higher H-indices demonstrated improved neurological outcomes (p = 0.01) compared to surgeons with lower H-indices, without any significant difference in mortality. None of the other academic indicators were significantly associated with outcomes. Although prognostication following surgery for ruptured intracranial aneurysms primarily depends on clinical and radiological factors, the academic impact of the operating neurosurgeon may explain some heterogeneity in surgical outcomes.